Różne oblicza dżumy. Rzecz o uniwersalnym przesłaniu powieści Alberta Camusa = Various sides of a plague. Reflection on the universal message of Albert`s Camus novel - Bednarczyk-Stefaniak, Emanuela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article contains a study of a traumatic random event during which people confront the truths about their existence. Detailed analysis of the novel ?The plague? of Albert Camus led to the conclusion that the title plague - both as a plague and a metaphor for all misfortunes - places the community and the individual in the face of the experience of death that sets the order of the world and calls for acceptance attitude adequate to the knowledge of life. The analysis also shows that displacing the truth and escaping suffering or making you feel guilty for evil leads to negative consequences, and being guided by humanistic values allow to achieve inner peace and fulfillment.
Keywords: egzystencjalizm; Śmierć; epidemia; wojna; humanistyczne wartości; existence; death; epidemic; war; humanistic values